2018
DOI: 10.1111/cas.13520
|View full text |Cite
|
Sign up to set email alerts
|

Reverse of non‐small cell lung cancer drug resistance induced by cancer‐associated fibroblasts via a paracrine pathway

Abstract: The tumor microenvironment orchestrates the sustained growth, metastasis and recurrence of cancer. As an indispensable component of the tumor microenvironment, cancer‐associated fibroblasts (CAF) are considered as an essential synthetic machine producing various tumor components, leading to cancer sustained stemness, drug resistance and tumor recurrence. Here, we developed a sustainable primary culture of lung cancer cells fed with lung cancer‐associated fibroblasts, resulting in enrichment and acquisition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 56 publications
0
24
0
Order By: Relevance
“…Although the response to chemotherapy and radiotherapy in the early stage is relatively good, this treatment often leads to drug resistance during further treatment. Because of this effect, treatment strategies for lung cancer are relatively limited (Nakaoku and Kohno, 2017 ; Zhang et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the response to chemotherapy and radiotherapy in the early stage is relatively good, this treatment often leads to drug resistance during further treatment. Because of this effect, treatment strategies for lung cancer are relatively limited (Nakaoku and Kohno, 2017 ; Zhang et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al showed that IGF2 produced by cancer-associated broblasts (CAFs) induced autophagy in cancer cells post-radiation thereby promoting cancer cell recovery (35). Also, drug resistance in non-small cell lung cancer cells was observed, in icted by IGF2-AKT-Sox2-ABCB1 signaling in cancer cells co-cultured with CAFs (36). The survival of osteosarcoma cells, supported by IGF2, was dependent on enhanced autophagic ux and glutamine availability (23).…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted on various types of tumor cells have shown IGF-2 overexpression and increased IGF-1R receptor prevalence [121][122][123]. This fact is associated with a worse prognosis, shorter survival, and the development of resistance to chemotherapy [124,125]. Studies conducted to clarify the mechanism of IGF-2 activity have shown that it is necessary to understand the role of the individual components of the insulin/IGF signaling axis.…”
Section: Igf-2: Insulin-like Growth Factormentioning
confidence: 99%